A6 PREFERENCES FOR CARE FOR ACTIVE SYMPTOMS OF IBD IN A POPULATION BASED SAMPLE. (1st March 2018) - Bernstein, M T; Chhibba, T; Walker, J R; Ivekovic, M; Restall, G; Singh, H; Targownik, L E; Bernstein, C N
Abstract: Background: Persons with IBD frequently attend Emergency Departments (ED) when they are acutely ill though many could be better served in an alternative setting. Aims: To determine care preferences of people with IBD when seeking care for active symptoms. Methods: 1143 people 18–64 yrs in the population-based University of Manitoba IBD Research Registry participated in the survey (46% response rate). Results: 95% reported having a family doctor (FD), 10% a nurse practitioner, 61% a gastroenterologist (GE), and 18% a GI surgeon (GIS). However, only 42% reported being able to call a GE for advice in managing active symptoms. Only 29% felt that they could call a GE for an appointment within 1 week. Respondents indicated that if they were having severe symptoms, their most likely courses of action would be to make an appointment to see their regular GE/GIS (68%), phone regular GE/GIS (65%), go to an ED (49%), or search the Internet for information (48%). When asked to state most likely course of action, 38% reported they would call a GE/GIS, 36% would go to ED, and 17% would call their FD. If they were having mild/moderate symptoms the courses of action most commonly reported were to: wait it out as long as possible before going to a doctor (59%), make an appointment to see FD (46%), make an appointment to see regular GE/GIS (45%), or phone regular GE/GIS (42%); only 12% would go to ED. If only one choice was available 30% would call or make appointment with FD, 29% would call or make appointment with GE/GIS, and 17% would wait it out. When experiencing severe symptoms, those with Crohn's disease indicated they would be more likely to go to ED (OR=2.77, 95%CI=2.10–3.66) and less likely to adjust medications on their own (OR=.41, 95%CI=.31-.55) than those with UC. Those who had seen a GE within the year would be more likely to phone a GE/GIS (OR=4.00, 95%CI=2.94–5.44) or phone a nurse specialist (OR=1.74, 95%CI=1.28–2.35), and were less likely to call a FD (OR=.51, 95%CI=.39-.69) or go to a walk-in clinic (OR=.56, 95%CI=.37-.85) than those who had not seen a GE. However, having seen a GE within 1 year did not impact on the likelihood of stating they would attend an ED. When participants were asked, in the event they were having urgent problems with IBD, about their likelihood of seeking services not currently available but which could be made available in the future, they reported they were very likely or likely to use the following services: telephone contact with an IBD nurse (77%), phone contact with a GE (75%), and going to a walk-in GE clinic (71%). Conclusions: Persons with IBD are interested in choices other than accessing the ED when they are experiencing IBD symptoms; however, attending the ED remains a prominent choice. Improved access to specialized care may improve timeliness of care and reduce ED attendance. Funding Agencies: Abbvie Canada